Demand for storage of natural gas in Northwestern Europe: a simulation based forecast 2006-2030 - Felix Höffler; Madjid Kübler (Max Planck Institute for Research on Collective Goods, 2006)
The seasonal demand for natural gas requires supply flexibility. This swing is now largely provided in northwestern Europe by indigenous production. Declining reserves will increase the dependency on imports from far-off sources, which are less flexible. Hence, flexibility must be provided by additional storage. We estimate that in 2030 (depending on the desired level of security of supply) between 11 and 37 billion cubic meter of working gas volume will be required, in addition to the existing 37 billion cubic meters. This estimation is based on production and consumption forecasts for natural gas and observations of the relationship between the supply and demand of gas and the supply and demand of flexibility in the period 1995-2004. Scenarios and Monte Carlo simulations are provided to check for the robustness of our results. We also briefly discuss policy implications for the regulation of third party access to storage facilities.
Keywords: L98; L51; Q41; 330; Natural gas; storage; swing; third-party access